2010
DOI: 10.1080/ac.65.6.2059859
|View full text |Cite
|
Sign up to set email alerts
|

Chronotropic incompetence and coronary artery disease

Abstract: Chronotropic incompetence is associated with ventricular dysfunction in peak exercise and critical right coronary artery lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Previous studies suggested that several factors other than beta-blocker treatment could affect HR response during exercise, including age, body weight, functional capacity, cardiac function, high max CK-MB, diabetes mellitus, and heart failure after MI [22,23,24,25,26]. The present study used MCR as an indicator of HR response, because MCR allows for the assessment of HR response without the effects of age, physical fitness, or functional capacity [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that several factors other than beta-blocker treatment could affect HR response during exercise, including age, body weight, functional capacity, cardiac function, high max CK-MB, diabetes mellitus, and heart failure after MI [22,23,24,25,26]. The present study used MCR as an indicator of HR response, because MCR allows for the assessment of HR response without the effects of age, physical fitness, or functional capacity [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…The slight increase in heart rate may be attributed to transient alterations in blood flow on the atrial wall 31 , progressive reductions in systolic volume or ventricular compliance alterations produced by diastolic dysfunction 32 .…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up analysis, limiting our observations to those with at least 2 years of follow-up did not materially change our results (data not shown). Since chronotropic incompetence is associated with prevalent coronary heart disease, 34 exclusion of participants who failed to reach 85% of age-predicted maximal heart rate not only decreased the possibility of reverse causation, but also reduced the chances for misclassifying fitness category. We also controlled for a number of potentially confounding variables in the analyses.…”
Section: Discussionmentioning
confidence: 99%